Development and Validation of a Food Frequency Questionnaire for Dietary Antioxidant Intake among Prediabetic Individuals in the South Indian Population - Sowmya R; Supriya V; Rajkumar M; Silambuselvi K (National Journal of Community Medicine, 2025)
Background: Prediabetes is a growing global public health concern, with dietary factors playing a major role in its progression to type 2 diabetes. Antioxidants can mitigate oxidative stress, a major contributor to prediabetes. This study developed a Food Frequency Questionnaire (FFQ) to assess the intake of key antioxidants, including vitamin C and E, selenium and zinc among prediabetic population in Chennai, India. Methodology: The food list was based on the Indian Food Composition Table (2017), and the portion sizes and frequencies were derived through a focus group discussion with registered dietitians and physicians. The FFQ intake data were compared with the mean of two 24-hour dietary recall (DR) using Pearson correlation analysis. Results: Strong correlations were observed for vitamin C (r=0.909) and vitamin E(r=0.915), and moderate correlations were observed for selenium (r = 0.696), and zinc (r = 0.706), with significant results (p < 0.001 for vitamin C, E, selenium, and p = 0.036 for zinc). Conclusion: The results indicated good agreement between the FFQ and DR, validating the developed FFQ as a reliable tool for estimating antioxidant intake in prediabetic individuals. This tool is useful for monitoring antioxidant intake in both clinical and public health settings.